Ethnic Identity And Subjective Well-Being In Students With Javanese And Chinese Backgrounds - Ismi Fatimah; Mugiarso, Heru (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
Students are inseparable from their cultural context. This study examined the difference of ethnic identity and subjective well-being between students with Javanese and Chinese ethnic backgrounds, based on two different previous research results. The research design was a comparative quantitative study with two independent samples. The study involved 101 high school students (71 ethnic Chinese students and 30 Javanese students). Sampling technique used was purposive sampling, based on the criteria decided by the researchers. The data collection tools used were the ethnic identity scale and subjective well-being scale. The analysis techniques used were percentage descriptive analysis and independent sample T-test analysis. Data showed a significant difference in ethnic identity between Javanese and Chinese students (t=2.011, p<0.05). Javanese students have a higher level of ethnic identity than Chinese. In addition, this study showed a difference in subjective well-being between Javanese and Chinese students (t=2.197, p<0.05). The results of this study have implications for counseling services to support subjective well-being, especially for ethnic Javanese and Chinese students.